The effects of U.S. poultry industry consolidation on employee productivity and labor costs - Tina L. Saitone; K. Aleks Schaefer; Daniel P. Scheitrum; Shawn Arita; Vince Breneman; Rebecca Nemec Boehm (Food Policy, 2026)

Vaginal polycyclic aromatic hydrocarbons (PAHs), HPV infection, and vaginal microbiome in firefighters: A cross-sectional study - Alexia L. Kafkoutsou; Marshley Stewart; Umer Bakali; Cynthia Campos Beaver; Gregory O’Connor; Erin N. Kobetz; Alberto J. Caban-Martinez; Sapna K. Deo; Sylvia Daunert; Natasha Schaefer Solle (Journal of Hazardous Materials, 2026)

The carbon dioxide radical anion as a reductant in water treatment and atmospheric chemistry: a review - Thomas Schaefer; Jonathan D. Raff; Mallikarjuna N. Nadagouda; Eric Lichtfouse; Dan Meyerstein; Hartmut Herrmann; Virender K. Sharma (Environmental Chemistry Letters, 2026)
The carbon dioxide radical anion, CO 2 ●− , is a highly reactive radical species involved in the reduction of the CO 2 greenhouse gas, organic synthesis, atmospheric aerosol chemistry, and treatment of halogenated compounds. In recent years, CO 2 ●− has emerged as a strong reductant, or single electron donor. Here we present techniques used to generate CO 2 ●− and we discuss applications to degrading pollutants such as halogenated alkanes. The potential occurrence of such reductions in water and aqueous aerosols is discussed, notably for the degradation of perfluoroalkyl substances. In the laboratory, CO 2 ●− is directly generated by either direct electrochemical reduction of CO 2 or hydrogen atom transfer of either formate salts with and without catalysts or ferrioxalate through photochemical or radiolytic processes. The CO 2 ●− has an ultraviolet spectrum, and CO 2 ●− vibration modes are characterized by fast kinetics using infrared and Raman spectroscopy. The second-order rate constants of the reactions of CO 2 ●− with halogenated alkanes, of -1.84 ± 0.22 V, are generally slower than that of the hydrated electron, of -2.87 V, and give a negative linear relationship with energy of lower unoccupied molecular orbital, suggesting single electron transfer mechanism in reducing the halogenated compounds.

Sackung at Bald Eagle ridge, central Colorado: An updated interpretation of ridge-spreading movement, structures, and mechanisms from 50 years (1975–2025) of U.S. Geological Survey research - Jeffrey A. Coe; Nikita N. Avdievitch; Kate E. Allstadt; Elaine A. Collins; Erin K. Jensen; Olivia J. Hoch; Lauren N. Schaefer; Chester A. Ruleman; Jonathan W. Godt; Vince Matthews (Engineering Geology, 2026)

The Earth’s magma ocean: Processes and current interpretations from an interdisciplinary perspective - Charles-Édouard Boukaré; Laura K. Schaefer; Hanika Rizo (Physics of the Earth and Planetary Interiors, 2025)

P19-20 A Multi-Substrate Approach for Simultaneous Assessment of CYP Enzymatic Activities in various In vitro Hepatic Models - P. El Azzi; K. Maunand; T. Heckel; C. Dahyot; J. Hemon; C. Touma; P. Daligaux; M. Pinaud; I. Ouhssain; E. Richard; E. Schaefer (Toxicology Letters, 2025)

HESI GTTC ring trial: Concordance between Ames and rodent carcinogenicity outcomes for N-nitrosamines (NAs) with rat and hamster metabolic conditions - Joel Bercu; Alejandra Trejo-Martin; Connie Chen; Maik Schuler; Jennifer Cheung; Tetyana Cheairs; Anthony M. Lynch; Dean Thomas; Andreas Czich; Aisar Atrakchi; Timothy J. McGovern; Robert H. Heflich; et al. (Regulatory Toxicology and Pharmacology, 2025)

Economic impacts of the Indian ban on non-Basmati rice exports - Kjersti Nes; K. Aleks Schaefer; Jisang Yu (Food Policy, 2025)

Exploring the transformative effects of calorie restriction on the lacrimal gland in adult mice - Olivier Mauduit; Prashant Kumar; Kaitlin K. Scholand; Emre Aksan; Laura Schaefer; Anmar Abu-Romman; Vanessa Delcroix; Zhiyuan Yu; Aude I. Sindikubwabo; Ron Korstanje; Helen P. Makarenkova; Cintia S. de Paiva (GeroScience, 2025)
Advanced age is one of the most recognizable risk factors for dry eye. Dry eye disease affects millions worldwide and can result from age-related lacrimal gland dysfunction, which correlates with a decline in lacrimal gland secretory cell function and chronic inflammation. This study investigated the potential of calorie restriction to maintain lacrimal gland and ocular surface health. Adult female C57BL/6 J mice were subjected to a 40% calorie restriction for 4 months, starting at 6–7 months and continuing until 10–11 months. These mice were compared to controls fed ad libitum. Bulk RNA sequencing of lacrimal glands, conjunctiva, and cornea subjected to calorie restriction compared to ad libitum revealed significant differentially expressed genes (DEGs). Pathways enriched in the upregulated DEGs indicate enhanced circadian rhythm, secretory functions, and lipid metabolism. These findings were confirmed using individual qRT-PCR and western blotting. In contrast, pathways enriched in the downregulated DEGs were associated with immune cell activation, adaptive immune responses, extracellular matrix remodeling, and metalloproteinase activity. Histological sections of calorie-restricted lacrimal glands revealed reduced mononuclear cell infiltration and fewer positive cells for CD4, CD19, and MHC II than in ad libitum lacrimal glands. Calorie restriction also prevented age-related corneal barrier dysfunction and mitigated age-related conjunctival goblet cell loss, hallmarks of dry eye disease. These findings suggest that calorie restriction supports lacrimal gland and ocular surface health by reducing inflammation and extracellular matrix remodeling and by enhancing the lacrimal gland’s secretory function.

Aged regulatory T cells fail to control autoimmune lacrimal gland pathogenic CD4+ T cells - Kaitlin K. Scholand; Laura Schaefer; Gowthaman Govindarajan; Zhiyuan Yu; Jeremias G. Galletti; Cintia S. de Paiva (GeroScience, 2025)

Trade protection via tariff rate quota administration - K. Aleks Schaefer; Christopher A. Wolf (Food Policy, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Expanding the phytosanitary exclusion zone for Mexican avocados: Market impacts and unintended consequences - Irvin Rojas; K. Aleks Schaefer (Food Policy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Animal disease outbreaks and upstream soybean trade - Wuit Yi Lwin; K. Aleks Schaefer; Amy D. Hagerman (Food Policy, 2024)

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

Effects of daytime exposure to short-wavelength-enriched white light on alertness and cognitive function among moderately sleep-restricted university students - Mushfiqul Anwar Siraji; Leilah K. Grant; Alexandre Schaefer; Shamsul Haque; Shadab A. Rahman; Steven W. Lockley; Vineetha Kalavally (Building and Environment, 2024)

Serum per- and polyfluoroalkyl substance concentrations and longitudinal change in post-infection and post-vaccination SARS-CoV-2 antibodies - James Hollister; Alberto J. Caban-Martinez; Katherine D. Ellingson; Shawn Beitel; Ashley L. Fowlkes; Karen Lutrick; Harmony L. Tyner; Allison L. Naleway; Sarang K. Yoon; Manjusha Gaglani; Danielle Hunt; Jennifer Meece; et al. (Environmental Research, 2023)

Facilitation of non-indigenous ascidian by marine eco-engineering interventions at an urban site - Nina Schaefer; Francisco Sedano; Melanie J. Bishop; Kate Dunn; M. Hank Haeusler; K. Daniel Yu; Yannis Zavoleas; Katherine A. Dafforn (Biofouling, 2023)

The role of eating expectancies and eating motives in the association between mood and loss-of-control eating: A national sample daily diary study - Emily K. Burr; Robert D. Dvorak; Ardhys N. De Leon; Angelina V. Leary; Roselyn Peterson; Lauren M. Schaefer; Stephen A. Wonderlich (Appetite, 2023)

Efficacy of Corsi Block Tapping Task training for improving visuospatial skills: a non-randomized two-group study - Sydney Y. Schaefer; Andrew Hooyman; Nicole K. Haikalis; Randy Essikpe; Keith R. Lohse; Kevin Duff; Peiyuan Wang (Experimental Brain Research, 2022)

AudioGene: refining the natural history of KCNQ4, GSDME, WFS1, and COCH-associated hearing loss - Ryan K. Thorpe; W. Daniel Walls; Rae Corrigan; Amanda Schaefer; Kai Wang; Patrick Huygen; Thomas L. Casavant; Richard J. H. Smith (Human Genetics, 2022)

The natural history of OTOF-related auditory neuropathy spectrum disorders: a multicenter study - Ryan K. Thorpe; Hela Azaiez; Peina Wu; Qiuju Wang; Lei Xu; Pu Dai; Tao Yang; G. Bradley Schaefer; B. Robert Peters; Kenny H. Chan; Krista S. Schatz; Joann Bodurtha; et al. (Human Genetics, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

MYT1L-associated neurodevelopmental disorder: description of 40 new cases and literature review of clinical and molecular aspects - Juliette Coursimault; Anne-Marie Guerrot; Michelle M. Morrow; Catherine Schramm; Francisca Millan Zamora; Anita Shanmugham; Shuxi Liu; Fanggeng Zou; Frédéric Bilan; Gwenaël Le Guyader; Ange-Line Bruel; Anne-Sophie Denommé-Pichon; et al. (Human Genetics, 2022)

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

The role of oxygen in stimulating methane production in wetlands - Jared L. Wilmoth; Jeffra K. Schaefer; Danielle R. Schlesinger; Spencer W. Roth; Patrick G. Hatcher; Julie K. Shoemaker; Xinning Zhang (Global Change Biology, 2021)
Methane (CH 4 ), a potent greenhouse gas, is the second most important greenhouse gas contributor to climate change after carbon dioxide (CO 2 ). The biological emissions of CH 4 from wetlands are a major uncertainty in CH 4 budgets. Microbial methanogenesis by Archaea is an anaerobic process accounting for most biological CH 4 production in nature, yet recent observations indicate that large emissions can originate from oxygenated or frequently oxygenated wetland soil layers. To determine how oxygen (O 2 ) can stimulate CH 4 emissions, we used incubations of Sphagnum peat to demonstrate that the temporary exposure of peat to O 2 can increase CH 4 yields up to 2000‐fold during subsequent anoxic conditions relative to peat without O 2 exposure. Geochemical (including ion cyclotron resonance mass spectrometry, X‐ray absorbance spectroscopy) and microbiome (16S rDNA amplicons, metagenomics) analyses of peat showed that higher CH 4 yields of redox‐oscillated peat were due to functional shifts in the peat microbiome arising during redox oscillation that enhanced peat carbon (C) degradation. Novosphingobium species with O 2 ‐dependent aromatic oxygenase genes increased greatly in relative abundance during the oxygenation period in redox‐oscillated peat compared to anoxic controls. Acidobacteria species were particularly important for anaerobic processing of peat C, including in the production of methanogenic substrates H 2 and CO 2 . Higher CO 2 production during the anoxic phase of redox‐oscillated peat stimulated hydrogenotrophic CH 4 production by Methanobacterium species. The persistence of reduced iron (Fe(II)) during prolonged oxygenation in redox‐oscillated peat may further enhance C degradation through abiotic mechanisms (e.g., Fenton reactions). The results indicate that specific functional shifts in the peat microbiome underlie O 2 enhancement of CH 4 production in acidic, Sphagnum ‐rich wetland soils. They also imply that understanding microbial dynamics spanning temporal and spatial redox transitions in peatlands is critical for constraining CH 4 budgets; predicting feedbacks between climate change, hydrologic variability, and wetland CH 4 emissions; and guiding wetland C management strategies.

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

Statistical Insights Regarding Fully Softened Shear Strength - Yuderka Trinidad González; Vernon R. Schaefer; Derrick K. Rollins (Geotechnical and Geological Engineering, 2021)

Beyond ecosystem modeling: A roadmap to community cyberinfrastructure for ecological data‐model integration - Istem Fer; Anthony K. Gardella; Alexey N. Shiklomanov; Eleanor E. Campbell; Elizabeth M. Cowdery; Martin G. De Kauwe; Ankur Desai; Matthew J. Duveneck; Joshua B. Fisher; Katherine D. Haynes; Forrest M. Hoffman; Miriam R. Johnston; et al. (Global Change Biology, 2021)
In an era of rapid global change, our ability to understand and predict Earth's natural systems is lagging behind our ability to monitor and measure changes in the biosphere. Bottlenecks to informing models with observations have reduced our capacity to fully exploit the growing volume and variety of available data. Here, we take a critical look at the information infrastructure that connects ecosystem modeling and measurement efforts, and propose a roadmap to community cyberinfrastructure development that can reduce the divisions between empirical research and modeling and accelerate the pace of discovery. A new era of data‐model integration requires investment in accessible, scalable, and transparent tools that integrate the expertise of the whole community, including both modelers and empiricists. This roadmap focuses on five key opportunities for community tools: the underlying foundations of community cyberinfrastructure; data ingest; calibration of models to data; model‐data benchmarking; and data assimilation and ecological forecasting. This community‐driven approach is a key to meeting the pressing needs of science and society in the 21st century.

Petrology and geochemistry of three Early Holocene eruptions from Makushin Volcano, Alaska - J. F. Larsen; Janet Schaefer; J. W. Vallance; O. K. Neill (Bulletin of Volcanology, 2020)

Anaerobic guilds responsible for mercury methylation in boreal wetlands of varied trophic status serving as either a methylmercury source or sink - Jeffra K Schaefer; Rose‐Marie Kronberg; Erik Björn; Ulf Skyllberg (Environmental Microbiology, 2020)
Summary Wetlands are common sites of active Hg methylation by anaerobic microbes; however, the amount of methylmercury produced varies greatly, as Hg methylation is dependent upon both the availability of Hg and the composition and activity of the microbial community involved. In this study, we identified the major microbial guilds responsible for Hg methylation along a trophic gradient composed of two sites and three different types of wetlands: a bog–fen peatland gradient and a black alder swamp, serving as net sources and a sink for methylmercury respectively. Iron‐reducing bacteria in the Geobacteraceae were important Hg methylators across all wetlands and seasons examined, as evidenced by abundant 16S rRNA and hgcA transcripts clustering with this family. Molybdate inhibited Hg methylation more efficiently in the peatlands than in the swamp, suggesting an increasing role of sulfate‐reducing bacteria and/or related syntrophs in the methylation of Hg with decreasing trophic status. Sulfate addition failed to increase Hg methylation rates in the peatlands, suggesting that SRBs/syntrophs were instead likely metabolizing alternative substrates such as syntrophic fermentation of organic compounds with methanogens. These results highlight the interconnectivity of anaerobic metabolism and importance of community dynamics on the methylation of Hg in wetlands with different trophic status.

E-vapor aerosols do not compromise bone integrity relative to cigarette smoke after 6-month inhalation in an ApoE–/– mouse model - Marie K. Reumann; Jenny Schaefer; Bjoern Titz; Romina H. Aspera-Werz; Ee Tsin Wong; Justyna Szostak; Victor Häussling; Sabrina Ehnert; Patrice Leroy; Wei Teck Tan; Arkadiusz Kuczaj; Christof Audretsch; et al. (Archives of Toxicology, 2020)
Cigarette smoke (CS) exposure is one of the leading risk factors for human health. Nicotine-containing inhalable products, such as e-cigarettes, can effectively support tobacco harm reduction approaches. However, there are limited comparative data on the effects of the aerosols generated from electronic vapor products (e-vapor) and CS on bone. Here, we report the effects of e-vapor aerosols and CS on bone morphology, structure, and strength in a 6-month inhalation study. Eight-week-old ApoE –/– mice were exposed to aerosols from three different e-vapor formulations—CARRIER (propylene glycol and vegetable glycerol), BASE (CARRIER and nicotine), TEST (BASE and flavor)—to CS from 3R4F reference cigarettes at matched nicotine concentrations (35 µg/L) or to fresh air (Sham) ( N = 10 per group). Tibiae were analyzed for bone morphology by µCT imaging, biomechanics by three-point bending, and by histological analysis. CS inhalation caused a significant decrease in cortical and total bone volume fraction and bone density relative to e-vapor aerosols. Additionally, CS exposure caused a decrease in ultimate load and stiffness. In contrast, bone structural and biomechanical parameters were not significantly affected by e-vapor aerosol or Sham exposure. At the dissection time point, there was no significant difference in body weight or tibia bone weight or length among the groups. Histological findings revealed microcracks in cortical bone areas among all exposed groups compared to Sham control. In conclusion, because of the bone-preserving effect of e-vapor aerosols relative to CS exposure, e-vapor products could potentially constitute less harmful alternatives to cigarettes in situations in which bone health is of importance.

Global vegetation biomass production efficiency constrained by models and observations - Yue He; Shushi Peng; Yongwen Liu; Xiangyi Li; Kai Wang; Philippe Ciais; M. Altaf Arain; Yuanyuan Fang; Joshua B. Fisher; Daniel Goll; Daniel Hayes; Deborah N. Huntzinger; et al. (Global Change Biology, 2020)
Plants use only a fraction of their photosynthetically derived carbon for biomass production (BP). The biomass production efficiency (BPE), defined as the ratio of BP to photosynthesis, and its variation across and within vegetation types is poorly understood, which hinders our capacity to accurately estimate carbon turnover times and carbon sinks. Here, we present a new global estimation of BPE obtained by combining field measurements from 113 sites with 14 carbon cycle models. Our best estimate of global BPE is 0.41 ± 0.05, excluding cropland. The largest BPE is found in boreal forests (0.48 ± 0.06) and the lowest in tropical forests (0.40 ± 0.04). Carbon cycle models overestimate BPE, although models with carbon–nitrogen interactions tend to be more realistic. Using observation‐based estimates of global photosynthesis, we quantify the global BP of non‐cropland ecosystems of 41 ± 6 Pg C/year. This flux is less than net primary production as it does not contain carbon allocated to symbionts, used for exudates or volatile carbon compound emissions to the atmosphere. Our study reveals a positive bias of 24 ± 11% in the model‐estimated BP (10 of 14 models). When correcting models for this bias while leaving modeled carbon turnover times unchanged, we found that the global ecosystem carbon storage change during the last century is decreased by 67% (or 58 Pg C).

Stereolithography-Based 3D Printed “Pillar Plates” that Minimizes Fluid Transfers During Enzyme Linked Immunosorbent Assays - Justin D. McCallen; Alison Schaefer; Phoebe Lee; Loretta Hing; Samuel K. Lai (Annals of Biomedical Engineering, 2017)

Detecting hybridization using ancient DNA - Nathan K. Schaefer; Beth Shapiro; Richard E. Green (Molecular Ecology, 2016)
It is well established that related species hybridize and that this can have varied but significant effects on speciation and environmental adaptation. It should therefore come as no surprise that hybridization is not limited to species that are alive today. In the last several decades, advances in technologies for recovering and sequencing DNA from fossil remains have enabled the assembly of high‐coverage genome sequences for a growing diversity of organisms, including many that are extinct. Thanks to the development of new statistical approaches for detecting and quantifying admixture from genomic data, genomes from extinct populations have proven useful both in revealing previously unknown hybridization events and informing the study of hybridization between living organisms. Here, we review some of the key recent statistical innovations for detecting ancient hybridization using genomewide sequence data and discuss how these innovations have revised our understanding of human evolutionary history.

Life cycle assessment use in the North American building community: summary of findings from a 2011/2012 survey - Maureen A. Olinzock; Amy E. Landis; Christi L. Saunders; William O. Collinge; Alex K. Jones; Laura A. Schaefer; Melissa M. Bilec (The International Journal of Life Cycle Assessment, 2015)

Isolation and characterization of microsatellite loci for the blackstripe topminnow Fundulus notatus and their variability in two closely related species - K. A. Feldheim; B. R. Kreiser; B. Schmidt; D. D. Duvernell; J. F. Schaefer (Journal of Fish Biology, 2014)
A total of 17 polymorphic microsatellite loci were isolated from the blackstripe topminnow Fundulus notatus . In a sample of 29 individuals, these loci were found to possess two to 19 alleles with expected heterozygosity values ranging from 0·212 to 0·919 and all but one of the loci conformed to Hardy–Weinberg equilibrium expectations. Many of these loci were polymorphic in the closely related species Fundulus olivaceus and Fundulus euryzonus providing a set of markers that should prove useful in future ecological and evolutionary studies of members of this species complex.

Analyzing the Practice of Life Cycle Assessment - Christi L. Saunders; Amy E. Landis; Laurel P. Mecca; Alex K. Jones; Laura A. Schaefer; Melissa M. Bilec (Journal of Industrial Ecology, 2013)
Summary Life cycle assessment (LCA) is a quantitative tool used to evaluate the environmental impacts of products or processes. With respect to buildings, LCA can be used to evaluate the environmental impacts of an entire building's life cycle. Currently LCA in the building area is used in a limited capacity, primarily to select building products. In order to determine the causality for the lack of whole‐building LCAs, focus groups with members of the architecture, engineering, and construction (AEC) communities were held. This article investigates the current level of knowledge of LCA in the AEC community and then discusses the benefits and barriers to the practice of LCA. In summary, the goal of the research was to identify why LCA is not used to its fullest potential in a whole‐building LCA. In an open forum and moderated setting, focus group participants were asked individually to self‐identify their experience with LCA, a brief education session on LCA was held, and then benefits and barriers to LCA were discussed. The focus group sessions were transcribed and systematically coded by social researchers in order to analyze the results. Hybrid flow and radar charts were developed. From the focus group results, the most important benefit to LCA was “provides information about environmental impacts.” The results did not identify a prominent barrier; however, building‐related metrics were ascertained to be one of the more crucial barriers. The benefits and barriers classified by this analysis will be utilized to develop a subsequent online survey to further understand the LCA and AEC community.

Expert assessment of vulnerability of permafrost carbon to climate change - E. A. G. Schuur; B. W. Abbott; W. B. Bowden; V. Brovkin; P. Camill; J. G. Canadell; J. P. Chanton; F. S. Chapin; T. R. Christensen; P. Ciais; B. T. Crosby; C. I. Czimczik; et al. (Climatic Change, 2013)

Erratum to: Dynamic life cycle assessment: framework and application to an institutional building - William O. Collinge; Amy E. Landis; Alex K. Jones; Laura A. Schaefer; Melissa M. Bilec (The International Journal of Life Cycle Assessment, 2013)

Dynamic life cycle assessment: framework and application to an institutional building - William O. Collinge; Amy E. Landis; Alex K. Jones; Laura A. Schaefer; Melissa M. Bilec (The International Journal of Life Cycle Assessment, 2013)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

Seven years of recent European net terrestrial carbon dioxide exchange constrained by atmospheric observations - W. PETERS; M. C. KROL; G. R. Van Der WERF; S. HOUWELING; C. D. JONES; J. HUGHES; K. SCHAEFER; K. A. MASARIE; A. R. JACOBSON; J. B. MILLER; C. H. CHO; M. RAMONET; et al. (Global Change Biology, 2010)
We present an estimate of net ecosystem exchange (NEE) of CO 2 in Europe for the years 2001–2007. It is derived with a data assimilation that uses a large set of atmospheric CO 2 mole fraction observations (∼70 000) to guide relatively simple descriptions of terrestrial and oceanic net exchange, while fossil fuel and fire emissions are prescribed. Weekly terrestrial sources and sinks are optimized (i.e., a flux inversion) for a set of 18 large ecosystems across Europe in which prescribed climate, weather, and surface characteristics introduce finer scale gradients. We find that the terrestrial biosphere in Europe absorbed a net average of −165 Tg C yr −1 over the period considered. This uptake is predominantly in non‐EU countries, and is found in the northern coniferous (−94 Tg C yr −1 ) and mixed forests (−30 Tg C yr −1 ) as well as the forest/field complexes of eastern Europe (−85 Tg C yr −1 ). An optimistic uncertainty estimate derived using three biosphere models suggests the uptake to be in a range of −122 to −258 Tg C yr −1 , while a more conservative estimate derived from the a‐posteriori covariance estimates is −165±437 Tg C yr −1 . Note, however, that uncertainties are hard to estimate given the nature of the system and are likely to be significantly larger than this. Interannual variability in NEE includes a reduction in uptake due to the 2003 drought followed by 3 years of more than average uptake. The largest anomaly of NEE occurred in 2005 concurrent with increased seasonal cycles of observed CO 2 . We speculate these changes to result from the strong negative phase of the North Atlantic Oscillation in 2005 that lead to favorable summer growth conditions, and altered horizontal and vertical mixing in the atmosphere. All our results are available through http://www.carbontracker.eu

Polymorphism at the avpr1a locus in male prairie voles correlated with genetic but not social monogamy in field populations - N. G. SOLOMON; A. R. RICHMOND; P. A. HARDING; A. FRIES; S. JACQUEMIN; R. L. SCHAEFER; K. E. LUCIA; B. KEANE (Molecular Ecology, 2009)
Integrative studies of genetics, neurobiology and behaviour indicate that polymorphism in specific genes contributes to variation observed in some complex social behaviours. The neuropeptide arginine vasopressin plays an important role in the regulation of a variety of social behaviours, including social attachment of males to females, through its action on the vasopressin 1a receptor (V1aR). In socially monogamous prairie voles ( Microtus ochrogaster ), polymorphism in the length of microsatellite DNA within the regulatory region of the gene ( avpr1a ) encoding the V1aR predicts differences among males in neural expression of V1aRs and partner preference under laboratory conditions. However, understanding the extent to which V1aR mediates variation in prairie vole social and reproductive behaviour observed in nature requires investigating the consequences of avpr1a polymorphism and environmental influences under ecologically relevant conditions. We examined the relationship between avpr1a length polymorphism and monogamy among male prairie voles living in 0.1 ha enclosures during a time similar to their natural lifespan. We found no evidence that avpr1a genotype of males predicts variation in social monogamy measured in the field but some indices of social monogamy were affected by population density. Parentage data indicated that a male’s avpr1a genotype significantly influenced the number of females with which he sired offspring and the total number of offspring sired. Total brain concentrations of V1aR mRNA were not associated with either male behaviour or avpr1a genotype. These data show that melding ecological field studies with neurogenetics can substantially augment our understanding of the effects of genes and environment on social behaviours.

Landscape genetics of California mule deer ( Odocoileus hemionus ): the roles of ecological and historical factors in generating differentiation - KATHERINE M. PEASE; ADAM H. FREEDMAN; JOHN P. POLLINGER; JOHN E. MCCORMACK; WOLFGANG BUERMANN; JEFF RODZEN; JIM BANKS; ERIN MEREDITH; VERNON C. BLEICH; ROBERT J. SCHAEFER; KEN JONES; ROBERT K. WAYNE (Molecular Ecology, 2009)
Landscape genetics is an emerging discipline that utilizes environmental and historical data to understand geographic patterns of genetic diversity. Niche modelling has added a new dimension to such efforts by allowing species–environmental associations to be projected into the past so that hypotheses about historical vicariance can be generated and tested independently with genetic data. However, previous approaches have primarily utilized DNA sequence data to test inferences about historical isolation and may have missed very recent episodes of environmentally mediated divergence. We type 15 microsatellite loci in California mule deer and identify five genetic groupings through a Structure analysis that are also well predicted by environmental data. We project the niches of these five deer ecotypes to the last glacial maximum (LGM) and show they overlap to a much greater extent than today, suggesting that vicariance associated with the LGM cannot explain the present‐day genetic patterns. Further, we analyse mitochondrial DNA (mtDNA) sequence trees to search for evidence of historical vicariance and find only two well‐supported clades. A coalescence‐based analysis of mtDNA data shows that the genetic divergence of the mule deer genetic clusters in California is recent and appears to be mediated by ecological factors. The importance of environmental factors in explaining the genetic diversity of California mule deer is unexpected given that they are highly mobile species and have a broad habitat distribution. Geographic differences in the timing of reproduction and peak vegetation as well as habitat choice reflecting natal origin may explain the persistence of genetic subdivision.

Sex Pheromone Components of Indian Gypsy Moth, Lymantria obfuscata - Regine Gries; Paul W. Schaefer; Roger Hahn; Grigori Khaskin; Gujjandadu Ramaseshiah; Balbir Singh; Gagandeep K. Hehar; Gerhard Gries (Journal of Chemical Ecology, 2007)

Analysis of mercuric reductase ( merA ) gene diversity in an anaerobic mercury‐contaminated sediment enrichment - Sinéad M. Ní Chadhain; Jeffra K. Schaefer; Sharron Crane; Gerben J. Zylstra; Tamar Barkay (Environmental Microbiology, 2006)
Summary The reduction of ionic mercury to elemental mercury by the mercuric reductase (MerA) enzyme plays an important role in the biogeochemical cycling of mercury in contaminated environments by partitioning mercury to the atmosphere. This activity, common in aerobic environments, has rarely been examined in anoxic sediments where production of highly toxic methylmercury occurs. Novel degenerate PCR primers were developed which span the known diversity of merA genes in Gram‐negative bacteria and amplify a 285 bp fragment at the 3′ end of merA . These primers were used to create a clone library and to analyse merA diversity in an anaerobic sediment enrichment collected from a mercury‐contaminated site in the Meadowlands, New Jersey. A total of 174 sequences were analysed, representing 71 merA phylotypes and four novel MerA clades. This first examination of merA diversity in anoxic environments suggests an untapped resource for novel merA sequences.

Biopharmaceutical Characterization of the Telomerase Inhibitor BRACO19 - S. Taetz; C. Baldes; T. E. Mürdter; E. Kleideiter; K. Piotrowska; U. Bock; E. Haltner-Ukomadu; J. Mueller; H. Huwer; U. F. Schaefer; U. Klotz; C.-M. Lehr (Pharmaceutical Research, 2006)

Behavior of bigeye (Thunnus obesus) and skipjack (Katsuwonus pelamis) tunas within aggregations associated with floating objects in the equatorial eastern Pacific - K. M. Schaefer; D. W. Fuller (Marine Biology, 2005)

Monitoring water content of rat lung tissuein vivo using microwave reflectometry - M. Schaefer; K. Nowak; B. Kherad; W. Gross; S. Post; M. M. Gebhard (Medical & Biological Engineering & Computing, 2004)

Remote activation of referred phantom sensation and cortical reorganization in human upper extremity amputees - S. M. Grsser; W. Mhlnickel; M. Schaefer; K. Villringer; C. Christmann; C. Koeppe; H. Flor (Experimental Brain Research, 2004)

Congruence on medication between patients and physicians involved in patient course - S. Foss; J. R. Schmidt; T. Andersen; J. J. Rasmussen; J. Damsgaard; K. Schaefer; L. K. Munck (European Journal of Clinical Pharmacology, 2004)

The integration of a major hepatitis B virus gene into cell-cycle synchronized carrot cell suspension cultures and its expression in regenerated carrot plants - J. Imani; A. Berting; S. Nitsche; S. Schaefer; W. H. Gerlich; K.-H. Neumann (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Bioequivalence of Topical Dermatological Dosage Forms-Methods of Evaluation of Bioequivalence - Vinod P. Shah; Gordon L. Flynn; Avraham Yacobi; Howard I. Maibach; Charles Bon; Nicholas M. Fleischer; Thomas J. Franz; Stanley A. Kaplan; Jeff Kawamoto; Lawrence J. Lesko; Jean-Paul Marty; Lynn K. Pershing; et al. (Pharmaceutical Research, 1998)

Detection of Giardia in Environmental Waters by Immuno-PCR Amplification Methods - Meena H. Mahbubani; Frank W. Schaefer III; Daniel D. Jones; Asim K. Bej (Current Microbiology, 1998)

Regulation of MMP-9 (92 kDa type IV collagenase/gelatinase B) expression in stromal cells of human giant cell tumor of bone - Velidi H. Rao; Rakesh K. Singh; Julia A. Bridge; James R. Neff; G. Bradley Schaefer; Duane C. Delimont; Christopher M. Dunn; Warren G Sanger; Bruce A. Buehler; Raymond Sawaya; Garth L. Nicolson; Jasti S. Rao (Clinical & Experimental Metastasis, 1997)

A device for the simulation of cardiac arrhythmias - S. Schaefer; M. Arditti; K. Stankus; D. Frost; W. Ganz; R. Vas (Annals of Biomedical Engineering, 1978)